2004
DOI: 10.1161/01.res.0000132745.76882.70
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis Inhibitor, TNP-470, Prevents Diet-Induced and Genetic Obesity in Mice

Abstract: Abstract-Adipose tissue growth has been proposed to involve recruitment of new blood vessels. Here, we test the hypothesis that delivery of an angiogenesis inhibitor in mice may prevent diet-induced obesity, the most common type of obesity in humans. We show that systemic administration of a selective angiogenesis inhibitor, TNP-470 (AGM-1470), prevents obesity in high caloric diet-fed wt mice as well as in genetically leptin-deficient ob/ob mice. Inhibition of obesity in mice by TNP-470 involves a reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
244
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 291 publications
(263 citation statements)
references
References 37 publications
15
244
0
4
Order By: Relevance
“…This is supported by reports that treatment with angiogenesis inhibitors resulted in weight reduction and adipose tissue loss, showing that adipose tissue mass is sensitive to angiogenesis inhibitors and can be regulated by its vasculature. [6][7][8] Extensive changes in ECM remodeling have also been shown to occur during adipose tissue growth. Two types of proteolytic systems, the plasminogen/plasmin (fibrolytic) and matrix metalloproteinase (MMP) systems, have been implicated in tissue remodeling, via degradation of ECM and basement membrane components, or activation of adipocyte growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by reports that treatment with angiogenesis inhibitors resulted in weight reduction and adipose tissue loss, showing that adipose tissue mass is sensitive to angiogenesis inhibitors and can be regulated by its vasculature. [6][7][8] Extensive changes in ECM remodeling have also been shown to occur during adipose tissue growth. Two types of proteolytic systems, the plasminogen/plasmin (fibrolytic) and matrix metalloproteinase (MMP) systems, have been implicated in tissue remodeling, via degradation of ECM and basement membrane components, or activation of adipocyte growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…A few other studies demonstrated that methionine aminopeptidase inhibitors, fumagillin and beloranib, could induce sustained weight reduction by reducing the production of new fatty acids in the liver and reducing the pathological angiogenesis in adipose tissue (24,25). Other groups have also demonstrated that angiogenesis inhibitors such as TNP-470, angiostatin, and endostatin exhibited antiobesity effects by inhibiting blood vessel growth in preclinical models (3,5). However, this line of inquiry has been challenged by the fact that energy expenditure requires active angiogenesis (6).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence reveals that adipose tissue development is associated with microvessel growth and requires vascular remodeling (4). In addition, the modulation of blood vasculature can directly affect adipose tissue metabolism (3,5,6). The crosstalk among many types of cells including adipocytes, endothelial cells (ECs), and stromal cells is mediated by multiple angiogenic factors that play pivotal roles in cooperatively modulating adipogenesis (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunomhistochemical staining was performed according to previously published methods [39][40][41] . Paraffin-embedded tumour issue sections (5 mm) were double-stained with anti-endomucin (1:400; eBioscience, 14-5851-85) and anti-aSMA (1:200; DAKO, M0851) antibodies, followed by staining with a mixture of secondary antibodies comprised of Alexa Fluor 555-labelled goat anti-rat (1:400; Molecular Probes) and Alexa Fluor 488-labelled donkey anti-mouse (1:400; Molecular Probes).…”
Section: Measurement Of Ctcs Using Facsmentioning
confidence: 99%